Fabrication and Photocatalytic Performance of ZnO-Biochar Composites for Eliminating Dye Waste - Desi Heltina; Danil Yoselino; Nabellia; Agustina Dumaria; Khairati Amila; Komalasari; Maria Peratenta Sembiring; Amun Amri; Zhong Tao Jiang (Communications in Science and Technology, 2025)
The synthesis of the ZnO-biochar composite from palm kernel shell biomass waste has been accomplished through the utilization of thesolvothermal method, yielding a satisfactory outcome. The resulting composite, a combination of ZnO and biochar, has been utilized in the degradation of methylene blue waste compounds. The objective of this research is to synthesize ZnO-biochar composites from palm shells, and to determine the optimal solvothermal temperature and duration. This research was initiated with the preparation of palm shells into biochar. Subsequently, the ZnO-biochar composite was synthesized with variable solvothermal temperatures and solvothermal times. The ZnO-biochar composite was characterized using analytical techniques including SEM-EDX, FT-IR, XRD, BET and UV-vis DRS. The most effective degradation of methylene blue was exhibited by the ZnO-biochar composite sample synthesized at a solvothermal temperature of 180 ̊C and a solvothermal time of 10 hours, achieving a degradation of 88.29%. The enhanced photodegradation performance of this composite sample is attributed to its high surface area, capacity for visible light absorption, and the dimensions of the active crystals, which can account for the high performance of the ZnO-biochar composite for photocatalytic degradation.